Inflation, Growth, and Employment : a series of research studies prepared for the Commission on Money and Credit - Conard, Joseph W.; Commission on Money and Credit (Englewood Cliffs, N.J., Prentice-Hall, 1964)
This volume was specifically prepared for the commission on money and credit as part of its research program leading to the publication in June 1961 of its final report: which was titled 'Money and Credit: their influence on jobs, prices and growth'.
Includes bibliographical references.
osc 14/8/17
Loans
Keywords: Inflation (Finance); Unemployed; Employment; Growth